OPTIMASI PENYERAPAN LIMBAH FOSFAT dan BOD INDUSTRI LAUNDRY DENGAN VARIASI MEDIA TANAM PADA SSF-WETLAND - Ernastin Maria; Amallia Puspitasari (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
Loundry industries have abad effect because most of them dump wastes into gutter or river without prior treatment. This study aims to test the potential of Canna Indica L. water plantsin reducing the pollutant content of loundry water (phosphate and BOD). The main research was done by the differene biomass of planting media which was used that is difference of gravel and sand media on SSF-wetland with title fraction and san media on SF-wetland for 10 days.Waste water used is effluent from Mira Loundry in Kanutan vilage, Sumbermulyo Bantul regency, witht the initial concentration of BOD as big as 231,359 mg/l and PO43-as 1,899 mg/l. The research has show that pollutants concentration in the water waste on the SSF-wetland is increase in the hydraulic retention time. For 10 days research the concentrate of BOD and PO43- decrease in SSF-wetland with canna Indica L. plants using of title fraction media, each become 96,680 mg/l (decrease 7,5%) and 1,715 mg/l (decrease 10%). Will using gravel media each become 67,80 mg/l (decrease 71%) and 1,75 mg/l (decrease 7%). From the data both planting media, gravel and title fraction, are considered to have good capability in phosphate waste removal in this system. For the most optimum BOD waste removal is using gravel media with decrease of BOD concentration become 67,880 mg/l.